Konsep Ta'dib Muhammad Naquib Al-Attas Dalam Pengembangan Karakter Peserta Didik: Analisis Filosofis-Pedagogis - Biltiser Bachtiar Manti; Abdul Muhyi; Yunus (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Abstract: This qualitative research with a pedagogical approach aims to examine the concept of Ta'dib (adab education) initiated by Muhammad Naquib Al-Attas as a fundamental framework in developing students' character. Al-Attas views the loss of adab values ​​as the root of the problem in Islamic education. The results of the study indicate that the concept of Ta'dib is oriented towards mastering correct knowledge to achieve stable deeds and noble morals based on faith. Ta'dib is not only a moral competence (akhlak) for educators and students, but also the key to the formation of a civilized personality (including friendliness, self-control, and spiritual awareness), with the ultimate goal of producing good humans who are aware of their responsibilities to God, themselves, society, and nature. The concept of Ta'dib has a close relevance to the goals of moral education (akhlak al-karimah) and requires a hierarchy of knowledge (fardhu 'ain is nobler than fardhu kifayah) as well as exemplary practices from educators. The implementation of Ta'dib values, such as the habit of prayer, memorizing the Quran, and civilized interactions, has generally been successful. However, during the COVID-19 pandemic, adab education faced significant challenges due to the shift to online learning (discussions, assignments) and the lack of optimal support from parents (especially those with limited time or professional resources). While online learning has the benefit of increasing parent-child interaction, this situation has resulted in a less conducive learning process and a decline in students' manners. Modifications to the learning process have been made to maintain curriculum targets and integrate life skills education.